Developing and Testing a Tool for Human Factors Design and Evaluation. (September 2013) - Ford, R. L.; Andre, T. S.; Sebok, A.; Meyer, R. E.; Laux, L.; Bzostek, J.; Wong, D. T.
Designing complex systems such as those used in spaceflight operations requires a coordinated effort among a variety of engineering teams. In these large-scale efforts, it is not uncommon for human factors issues to be missed until late in the design process, perhaps when an integration test is performed. To help solve this problem, TiER1 Performance Solutions and Alion Science and Technology developed H-FAST (Human Factors Analysis Support Tool). H-FAST is a research and development effort to increase human factors awareness among design engineers, facilitate communication between human factors engineers and design engineers, and promote the application of human factors best practices earlier in the design cycle. H-FAST also provides detailed guidance regarding human factors evaluations and the capability to store data and provide feedback on the results of these evaluations. In this paper, we describe the development strategy for H-FAST and report on our progress to date. In particular, we describe the identification and development of relevant human factors information to include in the tool, discuss the methods and results of a user test at NASA, and provide an overview of our plans forward.